International trade in tropical aquarium fish - International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre, 1979)
This is a market study on tropical aquarium fish in the USA Germany, France, UK, the Netherlands, Belgium, ans Switzerland.
Includes tables
II 17/01/2019
Loans
Keywords: Ornamental fish trade